풋콩용 내도복 대립 다수성 신품종 “녹원” - 고종민(Jong-Min Ko); 백인열(In-Youl Baek); 한원영(Won-Young Han); 강성택(Sung-Taek Kang); 김현태(Hyun-Tae Kim); 강남숙(Nam-Suk Kang); 신두철(Doo-Chull Shin); 정명근(Myoung-Gun Choung); 오세관(Sea-Kwan Oh); 오기원(Ki-Won Oh); 신상욱(Sang-Ouk Shin); 박금룡(Keum-Yong Park); et al. (Korean journal of breeding, 2008)
Nokwon, a new cultivar for vegetable soybean, was developed from the cross between Keunolkong and Hyangnam-1 and released in 2006. The pedigree of Nokwon, designated as Milyang 153 in 2003, was SS96425-2B-11-4-1-1-1. Nokwon, used as a vegetable soybean was characterized by dark green pod, large seed, very short plant height, and lodging resistance. Nokwon has determinate growth habit, white flowers, gray pubescence, oval leaf shape and brown pods at maturity. The mature seeds have a greenish yellow seed coat with brown hilum and yellow cotyledon. In Korea, Regional Yield Trials (RYT) for vegetable soybean from 2004 to 2006, Nokwon shows strong tolerance to soybean mosaic virus and lodging in fields. Fresh pods of Nokwon harvested at the beginning of August, and stem height was 11cm shorter than 45 cm of Hwaeomputkong. In the same tests, fresh pod of Nokwon (11.4 ton/ha) yielded 14% higher than Hwaeomputkong (10.0 ton/ha). Nokwon had 5.9 cm fresh pod length, 13.1 mm fresh pod width, 75.4 g seed weight per 100 green seed, 39.4% green seed protein content, and 17.3% green seed oil content.